MEASUREMENT OF PULMONARY PARENCHYMAL ATTENUATION IN HEALTHY THAI SUBJECTS: USE OF SPIROMETRIC GATING WITH QUANTITATIVE CT. - SUBHANNACHART, Ponglada; TUNGSAGUNWATTANA, Sutarat; ATHTAWET, Sumnieng (The ASEAN Journal of Radiology, 2023)
Objectives: To measure lung attenuation quantitatively in normal healthy Thai people and to measure the attenuation in various areas of the normal lung with quantitative high resolution CT. Materials and Methods: The subjects in this study were 154 healthy Thai volunteers. High resolution computerized tomography of the lung with spirometric gating (Pulmo CT) were obtained at level of the carina, 5 cm. above and 5 cm. below the carina. Scans were obtained at 50% vital capacity. Overall attenuation of the lungs and attenuation in various areas of the lungs were measured by using automatic fast contour tracing algorithms. Results: The mean attenuation of the lung parenchyma decreased when age increased. The mean attenuation of total lung parenchyma of healthy Thai subjects was -811 ±28 HU. The attenuation of anterior and posterior segments of the lung were not statistically different. The attenuation of the central part of the lung was more than in the peripheral part of the lung. Conclusions: Quantitative high resolution CT or Pulmo CT is non-invasive method for measurement lung tissue attenuation. This method is useful in early detection of diffuse lung lesions and in follow up study.